Rapid changes in river plume dynamics caused by advected wind‐driven coastal upwelling as observed in Lake Geneva. Issue 8 (9th June 2021) - Soulignac, Frédéric; Lemmin, Ulrich; Ziabari, Seyed Mahmood Hamze; Wynn, Htet Kyi; Graf, Benjamin; Barry, David Andrew
Abstract: Based on field investigations carried out in Lake Geneva during summer stratification in 2019, this study documents, for the first time, the rapid change of negatively buoyant river inflow dynamics caused by the passing of a coastal upwelling. Under calm conditions, the negatively buoyant Rhône River, entering at the eastern end of the lake, interacts with the lake density profile such that the river intrusion moves as an interflow in the thermocline layer straight out into the lake. A strong, large‐scale spatially homogeneous wind that lasts for several days causes a downward thermocline tilt at the western end of the lake, coastal downwelling on the northern shore, and coastal upwelling on the southern shore. This cold‐water upwelling progresses like a Kelvin wave around the lake after wind forcing ceases. When it arrives at the river inflow area, it homogenizes the lake water temperatures, and the river inflow transforms into an intrusion that spreads over the whole water column. Trapped by strong alongshore currents generated by the progressing coastal upwelling, the river plume is sharply deviated and flows along the shore in the nearshore zone, potentially bringing nutrients directly into the phototrophic near‐surface layer. Following the passage of the coastal upwelling, the river inflow transforms back into an interflow. This change in inflow dynamics, which is documented for five strong wind events between June and September by combining in situ measurements, remote sensing, and numerical simulation, can be expected to occur in other large lakes with comparable wind‐induced large‐scale thermocline displacement.